Regulatory and health technology assessment advice on postlicensing and postlaunch evidence generation is a foundation for lifecycle data collection for medicines. Issue 6 (24th April 2020) - Moseley, Jane; Vamvakas, Spiros; Berntgen, Michael; Cave, Alison; Kurz, Xavier; Arlett, Peter; Acha, Virginia; Bennett, Simon; Cohet, Catherine; Corriol‐Rohou, Solange; Du Four, Emma; Lamoril, Christelle; et al.
Abstract : The understanding of the benefit risk profile, and relative effectiveness of a new medicinal product, are initially established in a circumscribed patient population through clinical trials. There may be uncertainties associated with the new medicinal product that cannot be, or do not need to be resolved before launch. Postlicensing or postlaunch evidence generation (PLEG) is a term for evidence generated after the licensure or launch of a medicinal product to address these remaining uncertainties. PLEG is thus part of the continuum of evidence development for a medicinal product, complementing earlier evidence, facilitating further elucidation of a product's benefit/risk profile, value proposition, and/or exploring broader aspects of disease management and provision of healthcare. PLEG plays a role in regulatory decision making, not only in the European Union but also in other jurisdictions including the USA and Japan. PLEG is also relevant for downstream decision‐making by health technology assessment bodies and payers. PLEG comprises studies of different designs, based on data collected in observational or experimental settings. Experience to date in the European Union has indicated a need for improvements in PLEG. Improvements in design and research efficiency of PLEG could be addressed through more systematic pursuance of Scientific Advice on PLEG with single or multiple decision makers. To date, limited information has been available on the rationale, process or timing for seeking PLEG advice from regulators or health technology assessment bodies. This article sets out to address these issues and to encourage further uptake of PLEG advice.